2002
DOI: 10.1161/01.cir.0000038362.16740.a2
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Endogenous Endothelin-1 in Exercise-Induced Redistribution of Tissue Blood Flow

Abstract: Background-Endothelin-1 (ET-1) is a potent endothelium-derived vasoconstrictor peptide. Exercise results in a significant redistribution of tissue blood flow, which greatly increases blood flow in active muscles but decreases it in the splanchnic circulation. We reported that exercise causes an increase of ET-1 production in the internal organ and then hypothesized that ET-1 participates in the exercise-induced redistribution of tissue blood flow. We investigated the effects of acute endothelin-A (ETA)-recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
53
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 7 publications
5
53
0
Order By: Relevance
“…In endothelin receptor knockout mice, it was demonstrated that only ET A mediate ET-1-induced contractions of arteries of the gastric fundus [20]. ET A blockade with TA-0201 has been shown to improve the microcirculatory blood flow in the gastric mucosa of rats during treadmill running [21]. Anti-ulcer properties were also found for the ET A and ET B antagonist bosentan in indomethacin and water immersion-restrained stress rats [22].…”
Section: Discussionmentioning
confidence: 99%
“…In endothelin receptor knockout mice, it was demonstrated that only ET A mediate ET-1-induced contractions of arteries of the gastric fundus [20]. ET A blockade with TA-0201 has been shown to improve the microcirculatory blood flow in the gastric mucosa of rats during treadmill running [21]. Anti-ulcer properties were also found for the ET A and ET B antagonist bosentan in indomethacin and water immersion-restrained stress rats [22].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, endothelin-1 release may be stimulated by insulin, and may be involved in maintaining vasomotor tone at rest and during insulin stimulation [4,7]. Endothelin-1 is also thought to be involved in the redistribution of flow seen during exercise, causing con-striction in the gut and non-working muscles [8,9]. Although plasma endothelin-1 has a short half-life of approximately 3.6 min [10] and is cleared rapidly from circulation by the pulmonary, splanchnic and renal systems, endothelin-1 has long-lasting and potent vasoconstrictor effects [11].…”
Section: Introductionmentioning
confidence: 99%
“…KC is considered a precancerous stage of cancer [14][15][16]. Renal blood flow is reported to decrease to 20% during exercise, returning to a resting state after exercise [24]. This is similar to ischemiareperfusion and may increase generation of ROS after exercise [24].…”
Section: Discussionmentioning
confidence: 99%